Modelação de redes de distribuição de energia elétrica com carregamento não linear, incluindo elementos de regulação e compensação - Lima, Danusia de Oliveira de [UNESP] (2014)
In the last three decades the growth of the usage of equipments considered no linear loads in industrial processes, trade and residences has been significantly altered the conditions of charging/loading the electrical networks. In Brazil, these phenomena have been highlighted in the last decade, mainly in the south and southeast electrical networks, and this fact has been provoking significantly distortions in the waveforms and voltage along the electrical distribution feeders. On the other hand, the distribution companies have been facing costumers, users of their networks, even more demanding; therefore, those companies have been finding several challenges regarding the quality of voltage supply within the international standards. Having this context, and due to the necessity to reach satisfactory costumers' help, it is fundamentally important the load modelling to be fed and the suitable computational tools to simulate the harmonic flow produced by it, in accordance with all the important network charging, as their regulation elements and harmonic/reactive compensation. Considering the traditional computational tools of power flow analysis show results that once compared with the results measured in field show even more significant differences, those results imply in greater difficulties to the systems' operation adjustments. This paper proposes the development of a computational tool which may model the non linear supply networks, to analyse the harmonic flow and the consequent interactions with the network devices. The model of non linear loads are got through the direct mediations in the several Pontos de Acoplamento de Cargas (Point of Load Coupling) (PLC), through their Norton models, of which all the main distribution system devices are represented and modelled (substations, lines, switches, transformers, step voltage regulators, capacitors banks, and resonant filters), taking into consideration the real represented global ...